RESTORASI DAN PEMANFAATAN TEKNOLOGI PEMINDAIAN PADA ARSIP KARTOGRAFI DAN KEARSITEKTURAN DI BADAN ARSIP DAN PERPUSTAKAAN PROVINSI JAWA TENGAH - , ARSI MURTI HIDAYAH, Drs. Machmoed Effendhie, M.Hum. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This final report describes the restoration and utilization of scanning technology in cartography and architecture archives in Badan Arsip dan Perpustakaan (Arpus) Provinsi Jawa Tengah. Preservation is a crucial element in the whole operation of a records programme. Restoration is one of conservation method. Restoration treatment is intended to stabilize materials in their original format by chemical and physical means. This report uses three methods. The first method is obervation, directly used to determine the real situation while doing restoration and digitization. The second one is to interview the authorities at the restoration and digitization. The third method is use reference books. The three methods are used as basic source of information about the restoration and digitization. The main conclusion of this report is the restoration and utilization of scanning technology in cartography and architecture project is needed to improve and protect the physical archives. This report focuses spesial attention on manual lamination of the restoration process and digitize by scanning technology in Badan Arsip dan Perpustakaan (Arpus) Provinsi Jawa Tengah. Manual lamination methods consist of lamination with conqueror paper and lamination with lamatec cloth. The purpose of lamination is to offset the fragility of a document. Acid ity must be eliminated first with deacidification processes. One of other ways to protect document is to digitize archives by using SupraScan II. The advantages of digitizing is to duplicates of text and visual materials archived in a stabile medium, wider distribution of those same files to the public, and the afforded opportunity to combine digital images with other media to create dynamic virtual displays with great responsibility.